The Influence of Self-Efficacy on the Completion of Students' Thesis of IAIN Palangka Raya - Kurniawati, Nurlita; Qalyubi, Imam Qalyubi (Institut Agama ISlam Negeri Palangka Raya, 2024)
This thesis research discusses the influence of self-efficacy on the completion of students' theses at IAIN Palangka Raya. Self-efficacy is an individual's belief in his or her abilities that he or she is capable of carrying out a task in order to reach the point of achievement and success. This research aims to find out how much influence Self-Efficacy has on the completion of the IAIN Palangka Raya Student Thesis. The type of research used is quantitative with inferential methods focusing on revealing relationships between variables. The population in this thesis is students from the English Tadris Study Program, Faculty of Tarbiyah and Teacher Training IAIN Palangka Raya, Class of 2017, 2019, and 2020 with a total of 135 students. Sampling was carried out using Simple Random sampling with the Slovin formula. The sample used was 42 students. Data was obtained through questionnaire. Next, this research data was analyzed using the Simple Linear Regression Test. Because it only has one independent variable and one dependent variable. The results of research on the influence of self-efficacy on completing the IAIN Palangka Student Thesis show that Self-Efficacy (X) influences the completion of the Thesis (Y). Self-Efficacy influences student thesis completion by 57.1% while the rest is influenced by other factors that cannot be explained in this research.